'The people need civil liberties': trade unions and contested decolonisation in Singapore. (1st January 2016) - Curless, Gareth
Abstract: The history of Singapore has been dominated by a narrow range of issues: the process of constitutional development during the era of decolonisation, the alleged threat posed by the Malayan Communist Party (MCP) and the island's rapid social and economic transformation following separation from Malaysia in 1965. More recently, however, historians have sought to move away from this linear narrative of 'progress' associated with the 'Singapore Story' to focus on 'ordinary' Singaporeans and the role of often marginalised civil society groups. This article contributes to this growing body of revisionist literature by challenging conventional accounts that portray the organised labour movement as a stooge of the MCP. Instead, the article argues the trade unions' leaders associated with the opposition party Barisan Sosialis had their own distinct national liberation agenda, where the aim was not Marxist revolution but social and economic development, the promotion of multiracialism and the protection of civil liberties.